Aortic Regurgitation (Springer International Publishing, 2018)
This title is a comprehensive resource of aortic regurgitation suitable for both the novice and experienced practitioner. Detailed attention is given to the recently growing field of aortic valve-sparing surgery and aortic valve repair. Guidelines are also provided for general practitioners on how to treat patients after various aortic procedures. Also included are many operative photos, original medical illustrations and schematics. Aortic Regurgitation synthesizes current knowledge of aortic valve repair into an easy-to-follow, illustration-rich text. It is therefore an indispensable guide suitable for use by cardiologists and trainees in cardiology, cardiac surgeons, echocardiographers, general practitioners and radiologists. .